2017
DOI: 10.1099/ijsem.0.001607
|View full text |Cite
|
Sign up to set email alerts
|

Allodekkera sacchari gen. nov., sp. nov., a yeast species in the Saccharomycetales isolated from a sugar factory

Abstract: Three yeast isolates, G5-5(5)T, G5-9(3) and G5-9(4), were obtained from the sugar cane juice and waste from sugar production plant (Korach Industry Co., Ltd) in Korach province, Thailand. They were found to belong to the same species based on DNA sequence identity of the small subunit ribosomal RNA gene (SSU) and the D1/D2 region of the large subunit rRNA gene (LSU D1/D2). A blastn search of the GenBank database revealed they had 93 % nucleotide sequence identity to Dekkera bruxellensis for the SSU (1742 bp), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This genus belongs to the Pichiaceae family, which is a part of the Saccharomycotina subphylum (Kufferath & Van Laer, 1921;Riley et al, 2016). It is composed of six species (B. nanus, B. naardenensis, B. bruxellensis, B. anomalus, B. custersianus and B. acidodurans), with Allodekkera sacchari being the closest non-Brettanomyces species known to date (Jutakanoke et al, 2017;Péter et al, 2017) (Figure 1A). Recently, high quality genomes were obtained for five Brettanomyces species, revealing distant species separated in two clades with B. nanus and B. naardenensis on one hand, and B. bruxellensis, B. anomalus and B. custersianus on the other hand (Roach & Borneman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This genus belongs to the Pichiaceae family, which is a part of the Saccharomycotina subphylum (Kufferath & Van Laer, 1921;Riley et al, 2016). It is composed of six species (B. nanus, B. naardenensis, B. bruxellensis, B. anomalus, B. custersianus and B. acidodurans), with Allodekkera sacchari being the closest non-Brettanomyces species known to date (Jutakanoke et al, 2017;Péter et al, 2017) (Figure 1A). Recently, high quality genomes were obtained for five Brettanomyces species, revealing distant species separated in two clades with B. nanus and B. naardenensis on one hand, and B. bruxellensis, B. anomalus and B. custersianus on the other hand (Roach & Borneman, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Selected probiotic yeast isolates were cultured on YM agar under aerobic conditions at 30 °C for 48 h. A single colony of each isolate was selected for DNA extraction. Yeast DNA was extracted by the method previously described by Jutakanoke et al [ 30 ] and Manitis et al [ 31 ]. D1/D2 domain of 26S rDNA was amplified by PCR using F63 (5′-GCA TAT CAA TAA GCG GAG GAA AAG-3′) and LR3 (5′ GGT CCG TGT TTC AAG ACG-3′) as primers [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the same year, a methanol-assimilating anamorphic yeast was isolated from fruit waste in Brunei, Borneo, and was proposed as a novel yeast species, Candida borneonana [7]. Allodekkera sacchari , a novel yeast genus isolated from sugar production plant waste in Nakhon Ratchasima Province, Thailand was proposed in 2017 [8]. Recently, Limtongozyma siamensis and Limtongella siamensis , isolated from grease waste, were proposed as novel yeast genera in 2019 [9] and 2020 [10], respectively.…”
Section: Full-textmentioning
confidence: 99%
“…Many studies have reported that yeast can be found in diverse habitats such as soil [1], sea [2], parts of plants [3], insects [4] and waste [5][6][7][8][9][10]. The waste habitat offers a variety of environments and nutrient content and therefore it has become an interesting resource due to the many novel yeasts that have been discovered there.…”
mentioning
confidence: 99%